Applied Islamic Law of Trade and Finance : A Selection of Contemporary Issues - Billah, Mohd Ma'sum (Westview Press, 2007)
This book provides a clear and practical exposition of some contemporary practical issues in Islamic law of trade and finance. Comparison with civil law highlights the differences between the systems and greatly assists in the understanding of both systems. It covers topics such as commercial contracts, sale of goods, partnership, stock market, Islamic currency, takaful and the institution of zakat